Poverty Discriminating Factors between Aceh Province and Bangka Belitung Province: Discriminant Approach - Fransiska Simamora; Roosemarina Anggraini Rambe (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This study aims to determine the discriminating factors of poverty between Aceh Province and Bangka Belitung Province. Aceh Province has the highest poverty rate. In contrast, Bangka Belitung Province has the lowest poverty rate in Sumatra. Using time series, the research period is 12 years (2011-2022). The discriminating variables used in the research are GRDP per capita, HDI, investment, government spending per capita, gini ratio, and unemployment rate. The method applied is discriminant analysis. The results show that the discriminating variables are GRDP per capita, HDI, and unemployment rate. The local government of Aceh province should be able to create programs that can increase HDI and employment opportunities so that unemployment rates decrease and people's incomes increase.